2009
DOI: 10.2193/2008-284
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nest Predation by Alien Rodents and Avian Poxvirus in Conservation of Oahu Elepaio

Abstract: The Oahu elepaio (Chasiempis sandwichensis ibidis) is an endangered forest bird endemic to the Hawaiian island of Oahu (USA) and is threatened by nest predation from alien rodents and mosquito‐borne diseases. I investigated importance of these threats and evaluated success of conservation efforts from 1995 to 2008. I controlled rodents with snap‐traps and bait stations in 3 valleys and switched sites from non‐treatment to treatment over time. I mist‐netted and color‐banded 91 elepaio, inspected them for sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…In Hawai’i, introduced mammals such as black rats, feral cats, and mongooses prey on eggs, fledglings, or even adult birds [71]. One study of Oahu Elepaio ( Chasiempis ibidis ) found that rodent control improved female survival (nearly 50%), fecundity (> 100%), and nest success (near 100%) [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hawai’i, introduced mammals such as black rats, feral cats, and mongooses prey on eggs, fledglings, or even adult birds [71]. One study of Oahu Elepaio ( Chasiempis ibidis ) found that rodent control improved female survival (nearly 50%), fecundity (> 100%), and nest success (near 100%) [71].…”
Section: Discussionmentioning
confidence: 99%
“…In Hawai’i, introduced mammals such as black rats, feral cats, and mongooses prey on eggs, fledglings, or even adult birds [71]. One study of Oahu Elepaio ( Chasiempis ibidis ) found that rodent control improved female survival (nearly 50%), fecundity (> 100%), and nest success (near 100%) [71]. In contrast, no difference in nest success or abundance was detected in native forest birds during predator control at Hakalau Forest National Wildlife Refuge from 1996 to 1999 [71].…”
Section: Discussionmentioning
confidence: 99%
“…The primary threats to elepaio are nest predation by alien mammals, diseases carried by alien mosquitoes, and loss and degradation of habitat caused by feral ungulates, invasive alien plants, human development, and wildfires (VanderWerf and Smith 2002;U.S. Fish and Wildlife Service 2006;VanderWerf et al 2006;VanderWerf 2008VanderWerf , 2009. Information about phylogeography and population structure of elepaio is needed to inform management decisions and help develop the best possible conservation strategy (U.S. Fish and Wildlife Service 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A large suite of environmental factors have been found or are thought to reduce Maui parrotbill productivity in the wild: predation by native and alien vertebrates (Mounce 2008, VanderWerf 2009), restriction to suboptimal habitat inferred by the fossil record (Olson & James 1982), severe wind and rain storms during the breeding season (Simon et al 1997), and potentially inviable eggs related to small population genetics (Stone & Scott 1985). The relationship between parental investment and nest success has not been previously explored, especially in relation to severe weather.…”
Section: Discussionmentioning
confidence: 99%